Research Progress on Structure and Anti-Gynecological Malignant Tumor of Shikonin - Ke, Li-Na; Kong, Ling-Qi; Xu, Huan-Huan; Chen, Qin-Hua; Dong, Yun; Li, Bin; Zeng, Xiao-Hua; Wang, Hong-Mei (Frontiers in Chemistry, 2022)
Gynecological malignancy seriously threatens the physical and mental health of women. Shikonin is a naphthoquinone compound with a variety of biological activities. Studies have shown that shikonin can inhibit cell proliferation, promote cell apoptosis and induce cell necrosis. And in recent years, shikonin are also being increasingly used for the study of gynecological malignant diseases. Therefore, we reviewed the mechanism of action and structure optimization of shikonin in gynecological malignant tumors, in order to provide some reference for further research and development of related drug.